Mapeamento da trajetória jornalística : atuação e formação no contexto do jornalismo empresarial - Gehlen, Ivana de Jesus (2018)
The aim of this work is to chart the journalism track, through the observation of both academic education and professional performance, to verify its relationship with Enterprise Journalism and the activities of agencies of this sector. The theoretical development allows us to observe the original work of Journalism and the new professional segment. For this, a bibliographical research regarding the exercise of Journalism in new places in the market and also the teaching was carried out. The empirical research was constructed based on an overview of the communication agencies in Porto Alegre (RS) analyzing the actuation and academic education of the teams. We used the method of Cartography (Deleuze, Guattari, 2011 and Rosário, 2016), and Document Analysis techniques, according to Moreira (2005) and Gil (2008), besides the bibliographic research based mainly in the contextualizations developed by Melo (1971, 1990, 2001, 2002, 2004), Meditsch (1999, 2007, 2015), Barbosa (2007), Bueno (2003, 2005, 2007, 2009,2014), Chaparro (1993, 2004, 2009), Torquato (1984, 1986, 2004), among other authors.